Entomofauna diversity in areas of Caatinga under forest management in the semi-arid region of Ceará - Maia, Lilianne dos Santos; Leão, Maria Dalila Martins; Barbosa, Marianne Gonçalves; de Souza, Suyanne Araújo; Coutinho, Cristiane Ramos; Pastori, Patrik Luiz (Comunicata Scientiae, 2019)
The Caatinga is characterised by deciduous plant species. The practice in this ecosystem is the production of firewood which, when carried out with no technical criteria, contributes to a reduction in the biodiversity and degradation of the biome. Forest Management Planning has been approved by the Ministry of the Environment; a lower impact on the environment is expected, as there is still little information on the effect on biodiversity. The aim of this study was to evaluate the diversity of soil fauna in areas that adopt a Forest Management Plan. Five areas were selected that adopt Forest Management Planning: Area T1, unexploited for six months; Area T2, unexploited for 2-3 years; Area T3 unexploited for 5-6 years; Area T4, unexploited for 10-11 years; and the Control Area (unexploited). Four pitfall traps were installed in each area. The Shannon-Weaver (H’) Index, the Pielou Uniformity Index (e) and the Species Richness Index were calculated for the purpose of estimating the existing biodiversity. Total richness varied from 7 to 14 groups for the different collection periods and between the treatments; the highest value for the Shannon Index (0.72) was found during the dry/rainy transition period in the area that had been exploited 5-6 years earlier. The number of specimens is influenced by the various stages of wood exploitation.